Effects of Aminoglycoside Antibiotics on Human Embryonic Stem Cell Viability during Differentiation In Vitro - Divya S. Varghese; Shama Parween; Mustafa T. Ardah; Bright Starling Emerald; Suraiya A. Ansari (Hindawi Limited, 2017)
Human embryonic stem cells (hESCs) are being used extensively in array of studies to understand different mechanisms such as early human embryogenesis, drug toxicity testing, disease modeling, and cell replacement therapy. The protocols for the directed differentiation of hESCs towards specific cell types often require long-term cell cultures. To avoid bacterial contamination, these protocols include addition of antibiotics such as pen-strep and gentamicin. Although aminoglycosides, streptomycin, and gentamicin have been shown to cause cytotoxicity in various animal models, the effect of these antibiotics on hESCs is not clear. In this study, we found that antibiotics, pen-strep, and gentamicin did not affect hESC cell viability or expression of pluripotency markers. However, during directed differentiation towards neural and hepatic fate, significant cell death was noted through the activation of caspase cascade. Also, the expression of neural progenitor markers Pax6, Emx2, Otx2, and Pou3f2 was significantly reduced suggesting that gentamicin may adversely affect early embryonic neurogenesis whereas no effect was seen on the expression of endoderm or hepatic markers during differentiation. Our results suggest that the use of antibiotics in cell culture media for the maintenance and differentiation of hESCs needs thorough investigation before use to avoid erroneous results.